Diagnostic Methods Used in Detecting Multiple Myeloma in Paleopathological Research—A Narrative Review - Kinga Brawańska-Maśluch; Cyprian Olchowy; Grzegorz Mikita; Marta Wanat; Ada Świątko; Michał Krotliński; Martyna Byrska; Joanna Grzelak; Krzysztof Data; Paweł Dąbrowski (Heritage)
Objective: This study aims to analyze and evaluate the diagnostic methods used to detect multiple myeloma in paleopathological research. As a malignancy characterized by bone lesions, multiple myeloma presents unique opportunities for study through the paleopathological analysis of human skeletal remains. Methods: A literature review was conducted across PubMed, ScienceDirect, Embase, Scopus, Web of Science, and Google Scholar, focusing on macroscopic, radiological, and microscopic methods. A total of 43 original peer-reviewed studies published over six decades were selected. Results: The most commonly used diagnostic technique was macroscopic analysis of bone material, focusing on the characteristics of the lesions. Radiological methods, including X-ray, magnetic resonance imaging, computed tomography (CT), and micro-CT, provided complementary insights. Various microscopic techniques, chemical analyses, and fluoroscopy provided additional diagnostic detail. The diagnostic process is shaped by factors such as preservation, context, and access to technology; despite these variables, characteristic features of lesions were consistently recognized. Conclusion: This review highlights how macroscopic analysis remains central to diagnosis in paleopathology, with radiological and microscopic methods increasingly enhancing accuracy and interpretive depth. A multidisciplinary approach, combining macroscopic, radiological, microscopic, and chemical analyses where feasible, continues to strengthen paleopathological research and offers new insights into the historical presence of multiple myeloma.